(untitled) (Andamios, Revista de Investigación Social, 2016)
Contemporary research in psychology and neuroscience recognize the weight of emotions in the pursuit of our goals, in the development of our arguments and the quality of our social relationships. Philosophy and science no longer see reason as opposed to emotions; cooperation of emotions with cognition improves our practical rationality. Thus, the interest in the search for tools to educate our emotions becomes evident. Based on psychological, neurological and philosophical research on emotions, this article presents, from the perspective of philosophy of education, certain crucial elements that allow for the implementation of emotional education: self-conscious reflection, narrative, and the methodology of community of enquiry, which includes the former elements.